2008
DOI: 10.1258/ijsa.2008.007301
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of HIV-1-associated Kaposi's sarcoma among women and men in South Africa

Abstract: Despite the increase of HIV-1-associated Kaposi's sarcoma (KS), little is known about HIV-associated KS in the African setting, particularly among women. A descriptive study of the demographic, clinical, immunological and virological features of AIDS-associated KS from KwaZulu-Natal, South Africa was undertaken. Consecutively, recruited patients were clinically staged; CD4/CD8 cell counts, HIV-1 viral loads and clinical parameters were evaluated. Of the 152 patients (77 male and 75 female) 99% were black. Fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
20
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
10
20
2
Order By: Relevance
“…We confirmed the findings of other studies that advanced KS stage [10,11,18,19] predicts mortality, while chemotherapy [8,20] increases the chance of survival in KS patients. Unlike other South African studies [16,21] , we found no gender differences in mortality. Our study showed that both chemotherapy and radiation therapy were associated with improved survival.…”
Section: Discussioncontrasting
confidence: 99%
“…We confirmed the findings of other studies that advanced KS stage [10,11,18,19] predicts mortality, while chemotherapy [8,20] increases the chance of survival in KS patients. Unlike other South African studies [16,21] , we found no gender differences in mortality. Our study showed that both chemotherapy and radiation therapy were associated with improved survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Women had poorer 12-month survival not explained by ACTG prognostic factors or treatment arm. This finding builds on retrospective observations that women with HIV-KS have more aggressive disease and inferior outcomes than men 23-25 , and is the first prospective study demonstrating inferior outcomes in women despite comparable therapy.…”
Section: Discussionmentioning
confidence: 61%
“…In South Africa, it was estimated that the incidence of KS has doubled in men, while increasing by seven folds in women since the early 1990’s. Furthermore, women are also more likely than men to present with oral lesions when diagnosed with KS 22 . Nigerian women presented with KS at a younger age (~35 years) than men (~38 years) at the time of the first visit 14 .…”
Section: Discussionmentioning
confidence: 99%